A conformational switch‐based aptasensor for the chemiluminescence detection of microRNA. (9th July 2019) - Cai, Sheng; Ye, Jiawei; AL‐maskri, Abdu Ahmed Abdullah; Sun, Lianli; Zeng, Su
Abstract: A simple microRNA (miRNA) aptasensor has been developed combining the conformational switch of a streptavidin aptamer and isothermal strand displacement amplification. In the presence of its target miRNA, the allosteric molecular beacon (aMB) probe immobilized on the plate can be 'switched on' and release the streptavidin aptamer. At the same time, Klenow fragment (3′→5′ exo‐) is utilized to initiate DNA‐strand displacement, which starts the target recycling process. Based on the aptamer' high binding affinity and subsequent catalytic chemiluminescence (CL) detection, this CL strategy is highly specific in distinguishing mature miRNAs in same family. It exhibits a dynamic range of four orders of magnitude with a detection limit of 50 fM, and shows great potential for miRNA‐related clinical practices and biochemical research.